DIGITAL LITERACY AND EQUITY IN BASIC EDUCATION: A CASE STUDY OF ICT USE IN CAMEROON'S PUBLIC SCHOOLS - Akwane Mbozo'o (CV. Fahr Publishing, 2025)
This study explores the intersection of digital literacy and educational equity in Cameroon’s public schools. A mixed-methods approach was adopted, combining quantitative surveys of 400 participants (300 teachers and 100 administrators) with qualitative interviews and focus group discussions. The research assessed the availability, usage, and challenges of ICT integration in both urban and rural contexts. Results indicate a significant digital divide, with rural schools suffering from limited infrastructure, low teacher digital competence, and minimal ICT-based instruction. However, successful community-driven initiatives suggest that scalable, low-cost solutions are feasible when adapted to local needs. The findings emphasize the importance of comprehensive national strategies that address infrastructure, teacher training, and contextual curriculum development. These insights aim to support policy formulation for equitable access to quality digital education.